DINASTI ABBASIYYAH (750-1258 M) - Riskiyanda Wulandari; Nadia Febriyanti; Hermalisa; Ninda Audiska; Icha Fadillah Putri; Tria Desfika; Sirojul Fuadi (JURNAL ILMIAH NUSANTARA, 2025)
The Abbasid dynasty was one of the largest caliphate in Islamic history that brought Islamic civilization to its golden age (750–1258 AD). This research aims to examine political, economic, and scientific development policies during the Abbasid period which contributed greatly to world civilization. This study uses a qualitative method with a descriptive-historical approach through a literature study of the last five years. The results show that political stability, an orderly bureaucratic system, and economic progress have encouraged the development of science centers in Baghdad. Through the Baitul Hikmah institution, great scientists such as Al-Khawarizmi, Ibn Sina, and Jabir Ibn Hayyan were born who had a great influence on the development of global science. Nevertheless, the Abbasid dynasty suffered a setback due to internal conflicts, weak central power, and the Mongol invasion of 1258 AD that destroyed Baghdad. Although its political power collapsed, the scientific and cultural heritage of the Abbasid remains alive and has an impact on world civilization to this day.